From Artistic Creation to the Representation of the Imaginary, and Popular Culture in the Comic Books Genre - Santos, Milena dos; Silva, Cicero da [UNESP] (Univ Costa Rica, Editorial, 2022)
This paper analyzes elements that characterize aspects of artistic creation, mimesis, and representation of the imaginary, and popular culture in the Comic books genre produced by students of the Degree in Rural Education: Codes and Languages - Arts and Music at the Federal University of Tocantins. Methodologically, a participant research was carried out, with a qualitative approach. The results show that it is necessary to understand the aesthetics of the Comic books genre, its relationship with literature, as well as mimesis in artistic-literary production. And one of the ways to understand the representations of the imaginary and popular culture in comics is through aesthetic creation, and literature.
Keywords: Writing; Training; Visual Arts; Rural Education